5.2 Define Slope

6,871 views

Published on

Published in: Technology, Business
  • omg i like this website so fuckin much!!
    it has exactly what i need:o!!
       Reply 
    Are you sure you want to  Yes  No
    Your message goes here
  • Be the first to like this

5.2 Define Slope

  1. 1. 5.2 Defining Slope Student Study Guide
  2. 2. Examine the graphs below. Which lines have a positive slope? Negative slope? Zero or undefined? Negative Slope Zero Slope
  3. 3. Examine the graphs below. Which lines have a positive slope? Negative slope? Zero or undefined? Positive Slope 3. 4. Zero Slope
  4. 4. Slope = m = Rise Run
  5. 5. Use the graph to find the slope of each line. <ul><li>5. AB </li></ul>4 2 Slope 4 = 2 2 7. EF Slope Zero
  6. 6. Use the graph to find the slope of each line. <ul><li>9. IJ </li></ul>-5 2 Slope -5 2 11. MN Undefined
  7. 7. Find the slope of each line. <ul><li>13. Rise: -5; Run: -5 </li></ul>-5 = -5 15. Rise: -3; Run: 4 -3 4 1
  8. 8. Slope = y 2 - y 1 x 2 - x 1
  9. 9. Find the slope of the line containing each pair of points. <ul><li>17. A (3, 9), B(1, 5) </li></ul>Slope = y 2 - y 1 x 2 - x 1 x 1, y 1 x 2, y 2 5 - 9 = 1 - 3 -4 = -2 2
  10. 10. Find the slope of the line containing each pair of points. <ul><li>19. A (-3, 10), B(-5, -4) </li></ul>Slope = y 2 - y 1 x 2 - x 1 x 1, y 1 x 2, y 2 -4 - 10 = -5 - (-3) -14 = -2 7
  11. 11. Find the slope of the line containing each pair of points. <ul><li>21. A (3, -2), B(-1, 3) </li></ul>Slope = y 2 - y 1 x 2 - x 1 x 1, y 1 x 2, y 2 3 - (-2) = -1 - 3 5 -4
  12. 12. Find the slope of the line containing each pair of points. <ul><li>23. A (1, 8), B(-1, 7) </li></ul>Slope = y 2 - y 1 x 2 - x 1 x 1, y 1 x 2, y 2 7 - 8 = -1 - 1 -1 = -2 1 2
  13. 13. Find the slope of the line containing each pair of points. <ul><li>25. A (0, 4), B(3, -2) </li></ul>Slope = y 2 - y 1 x 2 - x 1 x 1, y 1 x 2, y 2 -2 - 4 = 3 - 0 -6 = 3 -2
  14. 14. Find the slope of the line containing each pair of points. <ul><li>27. A (-9, 9), B(7, -2) </li></ul>Slope = y 2 - y 1 x 2 - x 1 x 1, y 1 x 2, y 2 -2 - 9 = 7 - (-9) -11 16

×